METHODS FOR COMPUTING THEMARGINAL DISTRIBUTION OF RENEWAL PROCESSES - Suyono Suyono; Widyanti Rahayu (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2004)
In this paper we discuss methods for computing the marginal distribution of renewal processes by using transforms. Fordiscrete time renewal processes we use the double generating function whereas for continuous time renewal processes weuse the Laplace transform. Both of the transforms can be inverted numerically. In this paper we also discuss how tocompute the marginal distribution of non-parametric renewal processes.